Silangan Bonifacio urban tunnel development - Mison, Teresa Maria E.
Taking the thesis brief of this year: designing critical insertion and interventions, the designer sought to study a space that already longs to become PLACE. The Upper east (silangan) gate of Bonifacio Global City (BGC) was identified. Underneath C-5, is about 12 km of historical World War II tunnels, currently closed off and unused. BGC and other tourism related bodies hae expressed plans of creating a Bonifacio War Tunnel Museum that would showcase the tunnels and the main entrance, serving as a visual city marker for the upper east gate. The plans however plan to make the tunnel exclusive, ignoring that four out of the five tunnel exits are accessible only to East Rembo, a residential community categorized in Makati comprehensive Land Use Plan (CLUP) as urban decay. Makati on the other hand has programs like Special Precincts for Urban Renewal (SPUR) and Disaster Resiliency for Vulnerable Enclaves (DRIVE) that aim to develop East Rembo, to further integrate with the rest of the city. Assigned residential-commercial area in front of upper-east gate lot was considered. The project simply acknowledges that redesigning the tunnels for all of its users would be a wiser investment, and that the design paradigm of uncoordinated government effort must be addressed. This was accomplished by creating a (1) public underground, mixed use tunnel development (2) an iconic BGC entrance as both pedestrian access and main entrance and a (3) mixed-use condominium opposite the main entrance that includes the East Rembo SPUR site with the Tunnel's vision.